Enhancing supply chain management through information and communication technology based innovative solutions : the case of an international electronic firm in Malaysia / Devendran Rajangam - Rajangam, Devendran (2013)
This study is set to unravel the link between effective Supply Chain Management (SCM) practices and the overall performance of a selected electronic manufacturing firm in Malaysia. Past research has indicated that the inefficiency of many firms failing in SCM practices may be due to inability in incorporating technological capabilities (ICT Based Innovative Software Solutions for Information Sharing and Processing) in their SCM practices. Research evidence indicates that, the incorporation and effective usage of these technological capabilities for the benefit of information sharing and processing have turned around many electronics manufacturing firms into profitable organizations. This ‘case study like’ approach endeavors to explore how the so called technological capabilities, in the context of innovative software solutions for information sharing and processing help in the SCM process in electronics contract manufacturing firms. It analyses the relationships between internal and external integration processes of information sharing, their effect on firms’ performance and their contribution to the achievement of a competitive advantage. A well-known electronic manufacturing services company with its three different branches in Malaysia has been chosen as the sample for this fascinating study. Qualitative interviews were conducted with 15 senior level managers (5 from each of the three branches) who were involved in the SCM operations in the said firms. The findings focus on the proven success of ICT based innovative Software Solutions for Information Sharing and Processing. Several outstanding application systems such as, EDI, SCMDW, Quote win, ASPECT and SAP have been found to be effective in the advancement of Supply Chain processes. It is suggested that other key players need to adapt to new technologies in the SCM process to stay on as front runners in the industry.